ISU-ISU PEMBANGUNAN BERKELANJUTAN - Liris Windyaningrum, Theresia (Widya Warta, 2010)
A great deal of waste, especially the packaging one, was not optimally handled. This causes any movement of waste reduction to run just as a temporary act, while many countries already adopted advanced technologies to reduce waste. The purpose of this article was to examine the importance of sustainable management of packaging waste to support sustainable development. Generally the necessary effort possibly carried out to achieve development is the one through continual living environment education and its application in real action. The solution to support sustainable development needs integrated acts involving four sides – family, government, industry, and educational institution.